Kinematic changes at intensities proximal to onset of lactate accumulation - Shim, J.; Acevedo, E. O.; Kraemer, R. R.; Haltom, R. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to examine changes in selected kinematic variables at 3 running intensities proximal to the onset of blood lactate accumulation (OBLA; 4 mM of blood lactate). It was hypothesized that greater changes in lower body mechanics would occur when running faster than normal race pace compared to when running slower than race pace. Methods: Nine competitive male distance runners ran at 3 running intensities (RI): 1) each runner's VO2 at 10% below the VO2 at OBLA, 2) VO2 at OBLA, and 3) VO2 at 10% above the VO2 at OBLA. Selected kinematic and physiological variables were measured at each RI. Results: VO2 at RI 1, 2 and 3 was highly correlated with running speed (r=0.93). The blood lactate (BL) showed a nonlinear increase from RI 1 (2.9±0.8 mM) to 2 (4.1±0.9 mM) to 3 (6.7±1.8 mM). The vertical oscillation of center of gravity (VOCOG), stride frequency (SF), range of motion (ROM) of trunk angle, and maximal knee flexion during flight phase (MKFF) changed nonlinearly as did the BL. Significant relationships between BL and VOCOG (r=0.44) and between BL and SF (r=0.51) were found (ps<0.05). Conclusion: The findings show a possibility that lower body running mechanics have a relationship with BL.